Efeitos da carboxiterapia na cicatrização de feridas cutâneas em ratos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
This study aimed to evaluate the effects of carboxytherapy, infusion in the subcutaneous tissue of medicinal CO2, in the healing of cutaneous lesions in Wistars rats. This is an experimental and quantitative study, with a sample of 10 animals divided into a control group and a carboxytherapy group. All animals suffered a metallic punch injury of 5mm diameter in the dorsal region and the group with therapy treated for 10 consecutive days and then euthanized on the 11th day of the experiment. The region was photographed at various moments of the research to analyze the morphometric evolution of the lesion area and tissue samples containing the lesion were removed for microscopic analysis. . Histological analysis consisted of checking for collagen deposition, proliferation of fibroblasts and new blood vessels. The morphometric results showed that there was no increase in the velocity of closure of the lesion area. The carboxytherapy group presented higher total collagen deposition, type I and type III, and a greater proliferation of fibroblasts compared to the control group, but non-statistically significant data. The evaluation of the formation of new blood vessels had a positive result, with statistically significant numbers (p <0.05). At the end of this research, it was concluded that carboxitherapy may be a good treatment option for cutaneous wounds, especially in lesions with scarring due to microcirculatory deficit.
Keywords: Fisiologia; Carboxiterapia; Cicatrização; Feridas Cutâneas; CNPQ::GEOCIÊNCIAS::FISIOLOGIA::CARBOXITERAPIA::CICATRIZAÇÃO; FISIOLOGIA AMBIENTAL; BIOCIÊNCIAS